2001
DOI: 10.1089/152581601317210854
|View full text |Cite
|
Sign up to set email alerts
|

Soluble Fas (CD95) Is a Prognostic Factor in Patients with Metastatic Breast Cancer Undergoing High-Dose Chemotherapy and Autologous Stem Cell Transplantation

Abstract: The Fas/Fas ligand (FasL) system plays an important role in cellular apoptosis and is involved in cancer cell death induced by the immune system and anticancer drugs. Increased serum levels of soluble Fas (sFas) are associated with a number of different disease states and with tumor progression and metastasis in patients. In this study, we examined the plasma levels of sFas in 94 women with metastatic breast cancer undergoing high-dose chemotherapy (HDCT) treatment with autologous stem cell transplantation (AS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
18
0

Year Published

2004
2004
2011
2011

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 45 publications
0
18
0
Order By: Relevance
“…Additionally, they observed that tumor-infiltrating lymphocytes in close proximity to breast cancer cells expressing Fas ligand were predominantly apoptotic. Further, Bewick et al (38) observed an adverse effect of high pretransplant serum levels of Fas in 94 metastatic breast cancer patients who received high-dose chemotherapy. Our observations suggest that day ϩ15 absolute lymphocyte count may be a valid surrogate of those immune subsets that might be involved in immunity.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, they observed that tumor-infiltrating lymphocytes in close proximity to breast cancer cells expressing Fas ligand were predominantly apoptotic. Further, Bewick et al (38) observed an adverse effect of high pretransplant serum levels of Fas in 94 metastatic breast cancer patients who received high-dose chemotherapy. Our observations suggest that day ϩ15 absolute lymphocyte count may be a valid surrogate of those immune subsets that might be involved in immunity.…”
Section: Discussionmentioning
confidence: 99%
“…sFas inhibits the cell surface signal transduction by competitively binding and neutralizing FasL (Suda et al, 1993;Cascino et al, 1995;Natoli et al, 1995), which may correlate with cancer escaping immune surveillance and progression. Increased serum sFas level has been observed in patients with hepatocellular (Jodo et al, 1998), breast (Bewick et al, 2001), small cell lung cancer (SCLC) (Shimizu et al, 2005), esophageal (Gratas et al, 1998) and epithelial ovarian cancers (Chaudhry et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Zhu et al (2006) used immunohistochemistry and TdT-mediated dUTP nick end labeling (TUNEL) techniques to detect the changes of Fas, p53, Bcl-2, and apoptosis in 40 patients with uterine cervix carcinoma during radiotherapy, indicating a positive apoptosis rate, increased p53 and Fas expression, and significantly decreased Bcl-2 after radiotherapy. Several studies have demonstrated that apoptosis induced by chemotherapy involved the Fas/FasL system (Bewick et al, 2001;Shimizu et al, 2005;Naumnik et al, 2007;Chaudhry et al, 2008). Cytotoxic drugs lead to increasing FasL expression, which triggers tumor cells into apoptosis by binding Fas (Eichhorst et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Gastro-intestinal tumors may escape FasL-dependent immune-cytotoxic attack by overexpressing DcR3 that blocks FasL (25). Serum sFas levels may be a valuable clinical prognostic factor in predicting an outcome of disease progression for patients with metastatic breast cancer (26). Soluble FasL was eluted from the surface of uveal melanomas specifically inhibited cytotoxic T lymphocyte lysis of tumor cells pretreated with an inhibitor of metalloproteases (27).…”
Section: Discussionmentioning
confidence: 99%